1973
DOI: 10.1083/jcb.58.3.608
|View full text |Cite
|
Sign up to set email alerts
|

CONTRAST BETWEEN THE ENVIRONMENTAL pH DEPENDENCIES OF PROPHASING AND NUCLEAR MEMBRANE FORMATION IN INTERPHASE-METAPHASE CELLS

Abstract: In Chinese hamster Don cells, fusion of an interphase cell with a metaphase cell resulted either in prophasing of the interphase nucleus, including loss of the nuclear envelope (NE), or in the formation of a double membrane around the metaphase chromosomes . Only one of these phenomena occurred in a given interphase-metaphase (I-M) binucleate cell . At pH 7 .4, there was about an equal probability that either event could occur amongst the population of I-M cells . The effect of pH changes in the medium contain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
22
1

Year Published

1974
1974
1986
1986

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 17 publications
4
22
1
Order By: Relevance
“…Some of these characteristics distinguish them from the mitotic factors (40). The pH dependency ofthese factors is also in agreement with the results of the early cell fusion experiments of Obara and co-workers (21)(22)(23), which suggested that high pH favored "telophasing" and low pH "prophasing" or premature chromosome condensation . Our own studies (Hittelman and Rao, unpublished data) show that the frequency of premature chromosome condensation induction is much higher if a low pH is maintained during the collection of mitotic cells and subsequent fusion procedures.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Some of these characteristics distinguish them from the mitotic factors (40). The pH dependency ofthese factors is also in agreement with the results of the early cell fusion experiments of Obara and co-workers (21)(22)(23), which suggested that high pH favored "telophasing" and low pH "prophasing" or premature chromosome condensation . Our own studies (Hittelman and Rao, unpublished data) show that the frequency of premature chromosome condensation induction is much higher if a low pH is maintained during the collection of mitotic cells and subsequent fusion procedures.…”
Section: Discussionsupporting
confidence: 88%
“…Obara and co-workers (21)(22)(23) have reported that in certain cases in these multinucleate cells 712 THE JOURNAL OF CELL BIOLOGY " VOLUME 97, 1983 containing higher ratio of interphase cells, a membrane is formed around the metaphase chromosomes. Because of its resemblance to the process occurring in normal telophase, this process has been termed "telophasing" (21)(22)(23) . They have also demonstrated that the larger the ratio of interphase nuclei to chromosomes in the fused cells the greater the possibility that "telophasing" would occur rather than prophasing .…”
Section: Inhibitors Of Mitotic Factorsmentioning
confidence: 99%
“…Cells in log phase were obtained about 15 16 h after subculture of the Don line and about 20 21 h in the case of HeLa cells. The cultures were treated with Colcemid, 0.08 ~tg/ml, for 5 h. After trypsinization for 3 min at 37°C (16) the cells were washed once with prewarmed pH-adjusted medium containing Colcemid and resuspended in fresh medium at 37°C at the same pH (16).…”
Section: Virus and Cellsmentioning
confidence: 99%
“…Procedures for cell fusion and slide preparation were essentially the same as those described in previous papers (4,16). Approximately l07 log phase cells or a mixture of metapbase and interphase cells (5 × l0 s cells of each) were suspended at 37°C in a total of 1.0 ml of pHadjusted medium containing 2,000 hemagglutinating units (HAU) of inactivated Sendal virus and 0.08 #g of Colcemid.…”
Section: Cell Fusion and Slide Preparationmentioning
confidence: 99%
See 1 more Smart Citation